Sociodemographic characteristics and dependence levels in a group of people who smoke “rolled tobacco” in sanliurfa - Yanık, Medaim; Gencer, Mehmet; Ceylan, Erkan; Altındağ, Abdurrahman (Journal of Dependence, 2004)
Objective: Numerous studies have been conducted on the subject of smoking filter-tipped cigarettes in Turkey. However, to our knowledge, no studies have been undertaken regarding the smoking of hand-rolled tobacco. Smoking hand-rolled tobacco is common in Eastern and Southeastern Turkey. The purpose of this study was to investigate sociodemographic characteristics, smoking habits and dependence levels in people who smoke hand-rolled tobacco. Methods: Seventy-one subjects were selected randomly from people staying with patients in the hospital of Harran University Medical Faculty. Fagerstrom Tolerance Scale and a questionnaire about smoking hand-rolled tobacco which was prepared by the research team were applied to all subjects. Results: This study included 71 subjects (77.5% male, 22.5% female). The ages of subjects ranged from 16 to 74, the mean age was 45.6±14.0 years. Thirty-five percent of subjects were illiterate and 45% of them reside in the villages. 56.3% of subjects smoked more than 20 cigarettes a day. 26.8% of subjects had smoked for more than 30 years, 25.4% of them had been smoking for between 20 and 30 years. 93% smoked tobacco without filters, 87.3% smoked without a cigarette holder. Whereas 31% of subjects collected hand-rolled tobacco in a cigarette case, others rolled tobacco for each smoke. 35% of subjects sometimes smoked filtertipped cigarettes in addiction to hand-rolled tobacco. 55% of subjects had a family member who smoked hand-rolled tobacco. For 60.6% of subjects the reason for smoking hand-rolled tobacco was its low cost compared to filter-tipped cigarettes. 62.7% of subjects thought that hand-rolled tobacco is more harmful than filter-tipped cigarettes. The average score on the Fagerstrom Tolerance Scale in the study group was 6.47±2.46. These results suggested that 47.9% of subjects who smoked hand-rolled tobacco were physically dependent on nicotine. Men had significantly higher physical dependence rates than women (p=0.01). Conclusion: Being from rural areas and the low cost of hand-rolled tobacco are the important factors determining who smoked hand-rolled tobacco.